Computer-aided visualization aids for indoor rescue operation - Nguyen Thi Lan Truc (2010)
Finding a way out effectively and rapidly in emergency is always a problem for occupants who get trapped in an indoor environment. In such situation, rescuers often rely on emergency signs or verbal communication to direct the trapped people to the exits. However, many problems could arise during evacuation such as mobile signal interruption, low visible scene caused by dense smoke, etc. These problems might prevent the rescuers from communicating with Command Centre as well as to see the emergency signs and passageway clearly. Moreover, a complex spatial layout with obstructed spaces will add more difficult in deciding the correct way to take. To address the above problem, this thesis introduces an approach for effective rescue task in the context of way-finding in an indoor environment, namely inside vessels or buildings. The proposed approach takes into account how rescuers who are less familiar with the rescue area could immediately make sense of the spatial space while performing way-finding task regardless visibility of the environment. Based on principles and criteria of visual communication in emergency and human way-finding studies, this approach is investigated with the use of computer-aided visualization technologies and indoor trackers. To implement the approach, a visualization system is developed and integrated. Outcomes of the visualization system which are directional messages and aided information for way-finding performance are presented in terms of visual representations. It is real-time generated corresponding to the rescuer's information (e.g. current position and viewing orientation) and environment visibilities (e.g. clear, smoky). The visual representation is made up by combining a dynamic 2D You-Are-Here map integrated with directional signs superimposing on either 3D virtual environment or recording video of the real one. The visualization using virtual environment is called Virtual Reality (VR) display which can be used in case of low visual access or smoky scene. VR display enables the rescuer to recognize their ways easily since virtual scene is a 3D replication of the real one. The visualization using real scene is called Augmented Reality (AR) display which is applicable for wayfinding in clear scene.